2020
DOI: 10.1038/s41413-020-00115-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel negative regulatory mechanism of Smurf2 in BMP/Smad signaling in bone

Abstract: Transforming growth factor-β (TGF-β) and bone morphogenetic protein (BMP) play important roles in bone metabolism. Smad ubiquitination regulatory factors (Smurfs) regulate TGF-β/BMP signaling via ubiquitination, resulting in degradation of signaling molecules to prevent excessive activation of TGF-β/BMP signaling. Though Smurf2 has been shown to negatively regulate TGF-β/Smad signaling, its involvement in BMP/Smad signaling in bone metabolism has not been thoroughly investigated. In the present study, we sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Nedd4 exerts its molecular function mainly by ubiquitinating its substrates 39 , 40 . Ubiquitination of osteogenic-related proteins is closely related to bone growth and remodeling 41 , 42 . Zou et al reported that the E3 ubiquitin ligase WWP2 regulates craniofacial development through mono-ubiquitylation of goosecoid 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Nedd4 exerts its molecular function mainly by ubiquitinating its substrates 39 , 40 . Ubiquitination of osteogenic-related proteins is closely related to bone growth and remodeling 41 , 42 . Zou et al reported that the E3 ubiquitin ligase WWP2 regulates craniofacial development through mono-ubiquitylation of goosecoid 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Smurf1, Smurf2 has been shown to negatively regulate BMP/Smad signaling via ubiquitination of Smad3 (Kushioka et al, 2020). In Xenopus embryos, Smurf2 also targets Smad1 for ubiquitination, similar to, but independent of, Smurf1 (Zhang et al, 2001).…”
Section: Bmp Signalingmentioning
confidence: 99%
“…TGF- β signaling targeting COL5A1 shows osteogenic potential by treatments in vitro and in vivo. It also has found that the TGF- β response element (T β RE) exists in the upstream of the Col1α1 transcription start site in mice, and it could activate Col1α with the assistance of various receptor complexes, such as Smad2/Smad3/Smad4 [ 68 , 69 ]. And Smad7 inhibits the activity of the Smad2/Smad3/Smad4 complex ( Figure 4 ).…”
Section: Regulatory Factors With Circadian Rhythms In Bone Ecmmentioning
confidence: 99%